OPTIMASI GEL HAND SANITIZER OLEUM CITRI DENGAN KOMBINASI CARBOPOL, LIDAH BUAYA DAN TEA MENGGUNAKAN SIMPLEX LATTICE DESIGN - Joko Santoso; Heru Nurcahyo (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
Handsanitizer gel is composed of various additives such as geling agents, humectants and neutralizing / stabilizing agents. This material is certainly a basic ingredient that will affect the shape and quality of the preparation. Carbopol is very good when used, so that low levels can provide a significant viscosity response. Eleven hand sanitizer gel formulas with variations of carbomer, aloe vera and TEA were tested for their physical properties including organoleptic, homogeneity test, pH test, spreadability and adhesion test . The optimum formula is obtained by using the Simplex Lattice Design method, then the results are analyzed using an expert design software. The optimum formula for oleum citri hand sanitizer gel contains 0.944 with carbomer 0 (0.5%), aloe vera 0.471 (5.239%) and TEA 0.529 (0.576%). The t test results obtained showed insignificant differences between the response of the physical properties of the experiment results and the prediction software. Keywords: hand sanitizer gel, carbomer, aloe vera, TEA, Simplex Lattice Design.